(untitled) (Ustozlar uchun, 2025)
This article explores how corpus linguistics contributes to the study of historical language change, focusing on how digital corpora reveal patterns of linguistic evolution over time. Corpus-based methods allow researchers to examine authentic texts from different historical periods, tracing changes in vocabulary, grammar, and meaning. Using large, time-structured corpora such as the Helsinki Corpus, the Corpus of Historical American English (COHA), and the ARCHER Corpus, linguists can quantify language development from Old English to Modern English.